Exploring the Level and Primary Causes of Speaking Anxiety in Thesis Seminar Among EFL Students - Nur Rahim Noryani; Bibit Suhatmady; Dian Anggriyani (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2020)
Speaking anxiety in this research was interpreted as a feeling of nervousness when EFL students were speaking English while delivering the material in the thesis seminar. The purposes of this study were (1) to find out the levels of speaking anxiety in thesis seminars and (2) to find out the primary factors that influence speaking anxiety in thesis seminar among EFL students of English Department at Mulawarman University. The design of this study was the quantitative method. This study dealt with a descriptive quantitative approach. In this case, the researcher took 56 students; 36 students in the academic year 2015 and 20 students in the academic year 2016 from English Department at Mulawarman University as the sample to investigate the level and primary causes of EFL students' public speaking anxiety in thesis seminar. In this study, the quantitative data from the result of the adapted Public Speaking Class Anxiety Scale (PSCAS) questionnaire proposed by Yakihong and Usaha (2012) was analyzed by descriptive statistic SPSS 26. The results of SPSS 26 indicated that there were 62.8% of students experienced a medium level of public speaking anxiety in the thesis seminar. Furthermore, it was found that lecturers’ or contributors’ characteristics (LCC) became the primary factor that contributed to influence speaking anxiety in thesis seminar